2017
DOI: 10.1016/j.physd.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the phase motion in race-track microtrons

Abstract: We model the phase oscillations of electrons in race-track microtrons by means of an area preserving map with a fixed point at the origin, which represents the synchronous trajectory of a reference particle in the beam. We study the nonlinear stability of the origin in terms of the synchronous phase —the phase of the synchronous particle at the injection. We estimate the size and shape of the stability domain around the origin, whose main connected component is enclosed by an invariant curve. We describe the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…The most dangerous nonlinear resonances causing beam losses are the third-order and forth-order resonances situated for ν = 1 at the synchronous phase values ϕ s = 25.5 • and ϕ s = 17.7 • , respectively. If the number of orbits is not small, 10 or more, and if ϕ s is close to the resonance, then the stable phase oscillation region narrows sharply [25][26][27]. Previous studies have also revealed quite non-trivial properties of the stable phase oscillation region in RTMs.…”
Section: Common Problems Of CM and Rtmmentioning
confidence: 99%
See 1 more Smart Citation
“…The most dangerous nonlinear resonances causing beam losses are the third-order and forth-order resonances situated for ν = 1 at the synchronous phase values ϕ s = 25.5 • and ϕ s = 17.7 • , respectively. If the number of orbits is not small, 10 or more, and if ϕ s is close to the resonance, then the stable phase oscillation region narrows sharply [25][26][27]. Previous studies have also revealed quite non-trivial properties of the stable phase oscillation region in RTMs.…”
Section: Common Problems Of CM and Rtmmentioning
confidence: 99%
“…Additionally, the stability region includes stable elliptic islands that are separated from the longitudinal acceptance which, in terms of the theory of dynamical systems, is a connected to a local stability domain that includes the synchronous trajectory (see Ref. [27] for details).…”
Section: Common Problems Of CM and Rtmmentioning
confidence: 99%